Assessment of nursing staff attitude regarding prevention of cervical cancer - Mayada Sobhy Zaki El-Bakry; Samia I. Hassan; Amina El-Nemer (BMC Nursing)
Abstract Background Cervical cancer is the third most commonly diagnosed cancer among women worldwide, while in Egypt, it is considered the 14th major contributor to female tumors. Aim of the study To assess nursing staff attitude regarding prevention of cervical cancer. Methods A descriptive cross-sectional study framework was executed in Mansoura University Hospital and six other buildings (psychiatry, burns, outpatient, special medicine, convalescence and radiation building), Mansoura city, Egypt, among 414 nursing staff who were chosen by using the convenience sampling technique. A structured interview questionnaire consisting of two parts was used to gather data from June 2024 and continued until the end of November 2024. Univariate analysis for descriptive data and bivariate analysis through the chi-square test were performed. Results The current research revealed that 76.3% of the studied nursing staff had a positive attitude toward the prevention of cervical cancer, while 69.3% of them agreed that cervical neoplasm is a highly preventable disease, and 71.7% of them agreed that cervical neoplasm is curable if detected early. Also, there was a statistically significant positive association between educational level and attitude (p < 0.001) and a statistically significant positive association between marital status and attitude (p < 0.031). Also, there was a statistically significant positive association between vaccination against HPV and positive attitude (p < 0.001), while there was a statistically significant positive association between positive attitude and cervical cancer screening (p < 0.012). Conclusion It is concluded that more than three-quarters of nursing staff demonstrated a positive attitude toward cervical cancer prevention, underscoring the need for continued educational interventions. Clinical trial number This study was not registered as a clinical trial as it does not involve an interventional design.